2006
DOI: 10.1002/biof.5520280206
|View full text |Cite
|
Sign up to set email alerts
|

Effect of polyclonal antisera to recombinant tNOX protein on the growth of transformed cells

Abstract: Previous reports have described a tumor-associated NADH oxidase (tNOX) and its continuous activation in transformed culture cells. Certain anticancer drugs have been shown to inhibit preferentially both the tNOX activity and the growth of transformed culture cells and the cytotoxicity is associated with the induction of apoptosis. To investigate the biological function of tNOX protein, we have raised polyclonal antisera against bacterial expressed tNOX protein and the antisera are able to recognize protein ban… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 28 publications
0
23
0
Order By: Relevance
“…2 A). Using an antiserum that recognizes multiple tNOX forms [13], we showed that the increase in PARP cleavage occurred concomitantly with a decrease in tNOX levels (Fig. 2B); moreover, this EGCg‐induced reduction in tNOX occurred in a time‐dependent manner (Fig.…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…2 A). Using an antiserum that recognizes multiple tNOX forms [13], we showed that the increase in PARP cleavage occurred concomitantly with a decrease in tNOX levels (Fig. 2B); moreover, this EGCg‐induced reduction in tNOX occurred in a time‐dependent manner (Fig.…”
Section: Resultsmentioning
confidence: 91%
“…Fetal bovine serum (FBS) and penicillin/streptomycin were obtained from GIBCO/BRL Life Technologies (Grand Island, NY). Antisera to tNOX were generated as described previously [13]. The anti‐PARP, anti‐phosphorylated p53, and anti‐rabbit IgG antibodies were from Cell Signaling Technology Inc. (Beverly, MA); the anti‐actin antibody was from Chemicon International Inc. (Tamekula, CA); the anti‐tubulin antibody was from Abcam Inc. (Cambridge, MA).…”
Section: Methodsmentioning
confidence: 99%
“…Dihexyloxocarbocyanine iodide (DiOC6(3)) was purchased from Calbiochem (San Diego, CA, USA). Antisera to tNOX used in Western blot analyses were generated as described previously [29] and the tNOX protein band recognized by this antisera was also identified by the commercial available anti-tNOX polyclonal antibody (Protein Tech Group, Inc. Chicago, IL) [39]. The anti-p53 and anti-mouse IgG antibodies as well as other chemicals were purchased from the Sigma Chemical Company (St. Louis, MO, USA), unless otherwise specified.…”
Section: Methodsmentioning
confidence: 99%
“…The NADH oxidase activity initially identified in rat liver plasma membranes is responsive to growth factors and hormones (CNOX; ENOX1), whereas that from rat hepatoma is constitutive active [28] and has since been identified in various cancer cell lines [18,[29][30][31] and in the sera of cancer patients (tNOX; ENOX2) [32,33]. In fact, tNOX protein was originally purified from pooled cancer patient sera [34], suggesting its clinical relevance.…”
Section: Introductionmentioning
confidence: 99%
“…Mouse embryonic fibroblasts derived from transgenic mice overexpressing a truncated form of ENOX2 showed accelerated growth rates with respect to wild-type fibroblasts and enhanced invasiveness (315). In contrast, decreased cell growth and migration, as well as increased cell death, are observed when the function of ENOX2 is impaired, either by inhibiting the catalytic activity with (3)-epigallocatechin-3-gallate, capsaicin, phenoxodiol, or anti-ENOX2 antibodies (47,72,306,315) or by down-modulating its expression by RNA interference (173). Morré and colleagues also viewed ENOX2 as both (i) a noninvasive, circulating tumor marker (based on their description of several cancer-type specific ENOX2 isoforms) (119,307) and (ii) a potential antitumoral drug target, since this enzyme is blocked by quinone site inhibitors, which also exhibit anticancer activity (54,119,208).…”
mentioning
confidence: 91%